An Investigative and Comprehensive Study about Deregulation (Restructuring) of Indian Power Market - Ravindrakumar Yadav; Ashok Jhala (IAES Indonesian Section, 2017)
This paper is a discussion about the introduction of restructuring and deregulation in Indian Power System. In modern era, deregulation has an important impact on power sector. In this paper, recent use of deregulation in Indian Power Sector has been described and measures to be taken in order to improve deregulation are also suggested.